Methylation of Apoptosis-Associated Speck-Like Protein With a Caspase Recruitment Domain and Outcomes in Heart Failure - Butts, Brittany (J Card Fail, 2015)
BACKGROUND: Heart failure (HF) is associated with inflammation characterized by the formation the inflammasome, which triggers maturation of inflammatory cytokines. ASC, a vital component of the inflammasome, is controlled through epigenetic modification, which may be a candidate pathway for worsening HF. This study examined the inflammasome pathway in HF and the relationships between ASC CpG methylation and outcomes in HF. METHODS AND RESULTS: Stored samples from 155 HF outpatients (ejection fraction 29.9±14.9) were analyzed for % methylation of seven CpG sites in the intron region preceding exon-1 of the ASC gene. ASC methylation was inversely related to ASC mRNA (r=−.33,P<.001) and protein (r=−.464,P<.001). ASC methylation had a positive linear relationship with ejection fraction (r=.85,P<.001), quality of life (r=.83,P<.001), and six-minute walk test (r=.59,P=.023), and a negative linear relationship with depression (r=−.81,P<.001) and anxiety (r=−.75,P<.001). Higher ASC methylation was associated with a lower risk for clinical events (HR 0.16,P=.025), while higher protein (HR=1.78,P=.045) and mRNA expression (HR=1.18,P=.05) were associated with a greater risk. CONCLUSION: Increased methylation of CpG sites in the intron region of ASC is associated with improved outcomes in HF. The associated decrease in ASC expression implicates this inflammatory mediator as a possible driver of HF outcomes and may represent a therapeutic target.